Impact of Authoritarian Parenting Style on Neuroticism in Patients with Bipolar II Disorder: Mediating Influence of Maladaptive Coping Strategies - Naeem , Ruhma; Akram, Fozia (sourcecoder, 2025)
The objective of the present research was to examine the mediating influence of maladaptive coping strategies in the relationship between authoritarian parenting style and neuroticism among patients with Bipolar II Disorder. A matched pair sample was employed to compare patients with healthy controls in this comparative study. Data were collected through purposive sampling technique from 120 adults (60 patients with Bipolar II Disorder and 60 healthy controls). Diagnosed patients were recruited from hospitals on referral, with a controlled duration of illness (6 months to 3 years), and were further examined by the researcher through clinical interviews and mental state examinations. Healthy controls were selected from the community and educational institutions, matched with patients on age (18-40 years), gender (equal dissemination), and education (matric to graduation) to ensure comparability. Three Urdu-translated self-report measures were used; the parental authority questionnaire (Kausar & Shafique, 2008), the Big Five Inventory (Raiha, 2012), and the Cognitive Emotion Regulation Questionnaire (Butt, Khawer, Malik, & Sanam, 2012). The results indicated that there was significant positive impact of authoritarian parenting in constructing the contrary personality of patients with bipolar II disorder. Furthermore, the mediation analysis confirmed the influence of maladaptive coping strategies in the relationship between authoritarian parenting and neuroticism. Findings also indicated significant group differences: patients with Bipolar II Disorder scored higher on authoritarian parenting, neuroticism, and maladaptive coping strategies compared to healthy controls. Moreover, patients relied more heavily on maladaptive coping strategies than healthy controls. The study holds important implications for clinicians, providing deeper insight into the role of parenting and coping mechanisms in shaping the personality and psychopathology of individuals with Bipolar II Disorder, thereby facilitating more effective management strategies.